Candida albicans increases the pathogenicity of Staphylococcus aureus during polymicrobial infection of Galleria mellonella larvae. Issue 4 (18th February 2020) - Sheehan, Gerard; Tully, Laura; Kavanagh, Kevin A.
Abstract : This study detailed the responses of Galleria mellonella larvae to disseminated infection caused by co-infection with Candida albicans and Staphylococcus aureus . Doses of C. albicans (1×10 5 larva −1 ) and S. aureus (1×10 4 larva −1 ) were non-lethal in mono-infection but when combined significantly ( P <0.05) reduced larval survival at 24, 48 and 72 h relative to larvae receiving S. aureus (2×10 4 larva −1 ) alone. Co-infected larvae displayed a significantly higher density of S. aureus larva −1 compared to larvae infected solely with S. aureus . Co-infection resulted in dissemination throughout the host and the appearance of large nodules. Co-infection of larvae with C. albicans and S. aureus (2×10 4 larva −1 ) resulted in an increase in the density of circulating haemocytes compared to that in larvae infected with only S. aureus . Proteomic analysis of co-infected larval haemolymph revealed increased abundance of proteins associated with immune responses to bacterial and fungal infection such as cecropin-A (+45.4-fold), recognition proteins [e.g. peptidoglycan-recognition protein LB (+14-fold)] and proteins associated with nodule formation [e.g. Hdd11 (+33.3-fold)]. A range of proteins were also decreased in abundance following co-infection, including apolipophorin (−62.4-fold), alpha-esterase 45 (−7.7-fold) and serine proteinase (−6.2-fold). Co-infection of larvae resulted in enhanced proliferation of S. aureus compared to mono-infection and an immune response showing many similarities to the innate immune response of mammals to infection. The utility of G. mellonella larvae for studying polymicrobial infection is highlighted.